PERANCANGAN JALAN SULTAN SYARIF KASIM KELURAHAN TANJUNG KAPAL MENUJU DESA DARUL AMAN PADA KM 7 – KM 9 MENGGUNAKAN METODE PDT NO 14 TAHUN 2003 - Syarifudin, Syarifudin; Guswandi, Guswandi; Lisya, Mutia (Jurnal TeKLA, 2023)
Roads are the primary mean of transportation to reach a destination from one place to another espicially for the residents of  Tanjung Kapal Village – Darul Aman. The existing condition of Sultan Syarif Kasim Road, which is the research location, consist of class B aggregate as the subbase with a width of 6 meters, which is damaged, at 250 m long, the road is flooded when the high tide reaches 50 cm.            In the planning of the construction of rigid pavement on Sultan Syarif Kasim Road in Tanjung Kapal Village – Darul Aman Village, Bengkalis Regency the PDT method No.14-2003 is still used compared to other methods. Therefore, the author reviews, designs, and plans Sultan Syarif Kasim Road in Tanjung Kapal Village to obtain the desired pavement thickness and the required budget plan.            After calculating the thickness of the rigid pavement using the PDT method No.14 – 2003, the result obtained is 200 mm or 20 cm. With the result, the flooded location will no longer experience flooding due to tidal fluctuations. The total budget required for the plan is Rp 18,913,760,000.00.